In-situ formed graphene nanoribbon induced toughening and thermal shock resistance of spark plasma sintered carbon nanotube reinforced titanium carbide composite. (15th August 2017) - Sribalaji, M.; Mukherjee, Biswajyoti; Bakshi, Srinivasa Rao; Arunkumar, P.; Suresh Babu, K.; Keshri, Anup Kumar
Abstract: CNTs (2 wt%) reinforced TiC composite with WC (3.5 wt%) as sintering aid was densified using SPS technique at 1600 °C. In-situ formation of wide GNRs (Graphene nanoribbon) was observed due to CNT unzipping in TiC-WC-CNT (TWC) pellet. A phenomenal increase in fracture toughness (∼118%) was observed in TWC pellet compared to TiC. This significant improvement was due to novel toughening mechanisms like GNR grain wrapping, GNR crack bridging and crack bifurcation. Further, TWC pellet showed ∼48% improved thermal shock resistance compared to TiC, which could be due to the suppressed large thermal cracks by CNT and in-situ formed GNR. Graphical abstract: Highlights: Highly dense pellets of TiC, TiC-WC and TiC-WC-CNT were fabricated using SPS. In-situ formation of Wide GNRs is observed in TiC-WC-CNT composite. Drastic increase of ∼118% in fracture toughness was seen in TiC-WC-CNT composite. Thermal shock resistance of TiC-WC-CNT pellet was also increased by ∼48%.